(untitled) (Research, Society and Development, 2021)
Introduction: Flavonoids have received an increasing attention from the scientific community in the last decade due to its antioxidant and anti-inflammatory effects, showing benefits in various conditions, including major depression in animal models. The aim of this study was to review the evidence produced in the last 10 years regarding the antidepressant, antioxidant and anti-inflammatory effect of flavonoids in rodent models of depression. Material and methods: It was performed a systematic review to gather articles published between 2009 and 2019 that evaluate those effects of flavonoids in rodent models of depression. Results: 43 studies were included in the review. The most frequently studied flavonoids were hesperidin (14%) and baicalin (9%). The major natural source of flavonoids were citrus fruits (19%) and Scutellaria baicalensis Georgi (9%). Mice were used in the majority of the studies (86%). The majority of the studies did not use a specific model of depression (40%), and the most frequently used one was Chronic Unpredictable Mild Stress (21%). The most frequently used behavioral tests were forced swim test (81%), tail suspension test (56%) and open field test (51%). Discussion: Considering total tests, 93% of them presented an antidepressant activity, and all the studies that evaluated oxidative stress (37%) and inflammation (39%) found a significant antioxidant and anti-inflammatory result, respectively. Conclusions: Those findings demonstrate that the antidepressant, antioxidant and anti-inflammatory effects of flavonoids that were already evidenced in the study of other pathological conditions are also present in rodent depression models.